Pengaruh Partisipasi Anggaran Terhadap Kesenjangan Anggaran Dengan Komitmen Organisasi Sebagai Variabel Pemoderasi - Rinaldi Rinaldi; Henri Agustin; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2020)
This study aimed to determine the effect of budgetary participation to the budgetary slack to be moderated by the organizational commitment. This research was conducted in SKPD Pesisir Selatan District as much as 52 OPD. The respondents used in this study were 104 employees. Sample selection was done by using purposive sampling method. Data collection was done through questionnaire. The analysis technique used in this research is Moderated Regression Analysis.The results of this study found that, budgetary participation affect the budgetary slack and the organizational commitment can not moderate the influence of budget goal clarity for budgetary slack.